Intangible relationship value in service industries - Yang, AJ; Baxter, RA; Xu, Y (Australian and New Zealand Marketing Academy (ANZMAC), 2007)
This paper describes a differentiated replication, in a service industry, of the test of a model of intangible value in business to business buyer-seller relationships. It models value from the seller’s perspective. The original study was conducted by Baxter and Matear (2004) in the manufacturing sector. The current study finds that the model, synthesised from the intellectual capital literature, is broadly replicated in the business services sector, apart from one dimension of value, named “organisation”.